Gone With the Water: The Loss of Genetic Variability in Black and Gold Howler Monkeys (Alouatta caraya) Due to Dam Construction - Oklander, Luciana Inés; Caputo, Mariela; Fernández, Gabriela P.; Jerusalinsky, Leandro; de Oliveira, Silviene F.; Bonatto, Sandro L.; Corach, Daniel (Frontiers in Ecology and Evolution, 2022)
Black and gold howler monkeys (Alouatta caraya) inhabit several eco-regions in South America, with highest population densities in riverine forests. Dam construction for electricity production represents a severe human alteration of ecosystems, with consequences for primate conservation. To evaluate possible loss of genetic diversity in A. caraya, we analysed and compared the genetic structure of the species across 22 study sites in Argentina (14), Paraguay (1) and Brazil (7). Four of these study sites (referred as flooded) were sampled before dam-linked flooding, which most likely caused a drastic decline or functional extinction of these populations. Genetic variability of 256 individuals was evaluated using 10 autosomal microsatellites (STRs), and 112 individuals by sequencing a fragment of 507 bp of mtDNA D-Loop. DNA was extracted from tissue, blood and faecal samples. Significant higher values of genetic variability were observed for the flooded populations both in mtDNA and STRs. Population genetic structure showed a K=1, 2 or 5 depending on the method, separating Argentinian and Paraguayan sites from Brazilian sites and, in the case of K=5, two clusters were mostly represented by flooded populations. Isolation-by-Distance analyses showed that geographic distances influence gene flow. Analytical methods, such as Pairwise Fst´s and Nei´s and regression model of Harpending and Ward, were concordant in detecting significant genetic structuring between flooded and remaining sites examined. Although some sites have very low sample sizes, these samples are of great importance, since these sampling sites are currently flooded. Our results show that the study sites where dams were built had the greatest genetic diversity. As A. caraya is currently severely threatened by yellow fever outbreaks, the remaining populations may be more vulnerable to disease outbreaks due to impoverished genetic variability. Accordingly, it is essential to implement management actions to conserve remaining populations. Our results underline the importance for Environmental Impact Assessments to include data on the genetic structure of species at affected sites prior to their alteration or destruction; these genetic data are also remarkably important for determining where to relocate specific individuals to help avoid biodiversity loss.